2010
DOI: 10.1007/s10072-010-0273-x
|View full text |Cite
|
Sign up to set email alerts
|

Frovatriptan versus zolmitriptan for the acute treatment of migraine: a double-blind, randomized, multicenter, Italian study

Abstract: The objective of this study is to assess patients’ satisfaction with migraine treatment with frovatriptan (F) or zolmitriptan (Z), by preference questionnaire. 133 subjects with a history of migraine with or without aura (IHS criteria) were randomized to F 2.5 mg or Z 2.5 mg. The study had a multicenter, randomized, double-blind, cross-over design, with each of the two treatment periods lasting no more than 3 months. At the end of the study, patients were asked to assign preference to one of the treatments (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 12 publications
2
50
0
Order By: Relevance
“…The three studies shared a similar design, whose details are extensively reported in the original publications [8][9][10]. In brief, the studies included subjects of both genders, aged 18-65 years, with a current history of migraine with or without aura, according to International Headache Society criteria [12], and with at least one, but no more than six migraine attacks per month for 6 months prior to entering the study.…”
Section: Study Population and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The three studies shared a similar design, whose details are extensively reported in the original publications [8][9][10]. In brief, the studies included subjects of both genders, aged 18-65 years, with a current history of migraine with or without aura, according to International Headache Society criteria [12], and with at least one, but no more than six migraine attacks per month for 6 months prior to entering the study.…”
Section: Study Population and Designmentioning
confidence: 99%
“…Each patient received frovatriptan 2.5 mg or rizatriptan 10 mg (first study) [8], frovatriptan 2.5 mg or zolmitriptan 2.5 mg (second study) [9], and frovatriptan 2.5 mg or almotriptan 12.5 mg (third study) [10], in a randomized sequence. After treating 1-3 episodes of migraine in no more than 3 months with the first treatment, the patient had to switch to the other treatment and treated a maximum of three episodes of migraine in no more than 3 months with the second treatment.…”
Section: Study Population and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Frovatriptan has been evaluated in three double-blind, cross-over, headto-head trials versus rizatriptan, 33 zolmitriptan 34 and almotriptan. 35 The main aim of the study comparing frovatriptan and rizatriptan was to evaluate patient satisfaction for the treatment of acute migraine with either drug.…”
Section: Frovatriptanmentioning
confidence: 99%
“…Thus, the efficacy of these two triptans is similar but frovatriptan has a greater duration of action. 33 Frovatriptan (2.5 mg) and zolmitriptan (2.5 mg) were compared in a study of 133 patients with a history of migraine using similar endpoints to the trial reported by Savi et al 34 Both treatments were assigned similar preference scores (2.9±1.3 versus 3.0±1.3 for frovatriptan and rizatriptan, respectively). No significant differences were noted for pain-free or pain-relief episodes at 2 hours, recurrence rate, or sustained pain-free, but recurrence time favoured frovatriptan in particular between hours 4-16 (p<0.05).…”
Section: Frovatriptanmentioning
confidence: 99%